Does Etelcalcetide reverse myelofibrotic bone changes due to hyperparathyroidism? A case report - Panuccio, Vincenzo Antonio; Tripepi, Rocco; Postorino, Adele; Greve, Bruna; Sabattini, Elena; Oliva, Esther Natalie (Frontiers in Medicine, 2023)
Secondary hyperparathyroidism (SHPT) in dialysis is common. A young man on chronic hemodialysis with SHPT developed pancytopenia with resistant anemia requiring transfusions. A bone marrow biopsy showed grade 3 fibrosis, depleted cellularity, osteosclerosis, and decreased myelopoiesis. He initiated Etelcalcetide 7·5 mg 3 times weekly with improvement in SHPT concomitant with near normalization of blood counts. Marrow biopsy at 12 months showed clearance of marrow reticulin, improvement of osteosclerosis and normalization of bone trabeculae, cellularity and myelopoiesis. This is a unique case in which Etelcalcetide treatment is comparable to parathyroidectomy on SHPT and is associated with significant improvement in severe myelofibrosis.